Transenamel and Transdentinal Penetration of Hydrogen Peroxide Applied to Cracked or Microabrasioned Enamel - Briso, André Luiz Fraga [UNESP]; Lima, A. P. B. [UNESP]; Goncalves, R. S. [UNESP]; Gallinari, M. O. [UNESP]; Santos, Paulo Henrique dos [UNESP] (Operative Dentistry Inc, 2014)
The present study evaluated transenamel and transdentinal penetration of hydrogen peroxide during tooth whitening recognized in altered enamel by the presence of cracks or microabrasion. We used 72 experimental units (n=20) obtained from bovine incisors: GI-sound enamel; GII-teeth showing visible enamel cracks (4 mm to 5.7 mm in length); and GIII-microabrasioned enamel. The 12 remaining specimens were used to analyze the enamel surface morphology using scanning electron microscopy. The specimens were cylindrical and 5.7 mm in diameter and 3.5 mm thick. A product based on 35% hydrogen peroxide was used for bleaching, following the manufacturer's recommendations for use. To quantify the H2O2 penetration, the specimens were placed in artificial pulp chambers containing an acetate buffer solution. After bleaching, the solution was collected and adequately proportioned with leucocrystal violet, peroxidase enzyme, and deionized water. The resulting solution was evaluated using ultraviolet visible reflectance spectrophotometer equipment. The data were analyzed by analysis of variance (ANOVA) and Fisher's PLSD at a significance level of 0.05, and significant differences in the penetration of peroxide in different substrate conditions were observed (p<0.0001). The penetration of hydrogen peroxide was more intense in cracked teeth. The group in which the enamel was microabraded showed intermediate values when compared to the control group. Microabrasion and the presence of cracks in the enamel make this substrate more susceptible to penetration of hydrogen peroxide during in-office whitening.